Relationship between masticatory performance and the number of possible occlusal pairs present - Asis Macedo, Christian (2017)
Objective: To relate the masticatory performance to the number of posterior occlusal pairs present. Materials and Methods: Observational, prospective, transversal and analytical study. The sample consisted of 100 patients treated at the Specialized Dentistry Clinic of the San Martin de Porres University (USMP), from 2016 to 2017. A chewing test was performed to determine the masticatory performance (sieved test) with an artificial food, in subcategorized patients according to the Eichner Index. The test was applied to the patients grouped according to subcategories A1, B1, B2 and B3, distributing the total in 25 patients in each of them. Results: Comparing the masticatory performance of subcategories A1, B1, B2, B3, it was found that the masticatory performance of subcategory A1 (38.06%) was better than the subcategories B1 (69.43%), B2 (79.63 %), B3 (98.48%). At the same time, subcategory B1 obtained better masticatory performance than subcategories B2 and B3, as well as subcategor